2014
DOI: 10.1111/1462-2920.12563
|View full text |Cite
|
Sign up to set email alerts
|

Population structure and temporal maintenance of the multihost fungal pathogen Botrytis cinerea: causes and implications for disease management

Abstract: Summary Understanding the causes of population subdivision is of fundamental importance, as studying barriers to gene flow between populations may reveal key aspects of the process of adaptive divergence and, for pathogens, may help forecasting disease emergence and implementing sound management strategies. Here, we investigated population subdivision in the multihost fungus Botrytis cinerea based on comprehensive multiyear sampling on different hosts in three French regions. Analyses revealed a weak associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 68 publications
5
54
1
Order By: Relevance
“…cinerea proposed that host plant should be considered as a potent factor structuring populations of the pathogen, based on observed associations between patterns of population subdivision and the host of origin of isolates (see review and examples in Walker, ). In a previous (Walker et al ., ) and the present study, we confirmed that most of the genetic variation segregating in B . cinerea populations is explained by hosts, and that the effect of geography is weaker.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…cinerea proposed that host plant should be considered as a potent factor structuring populations of the pathogen, based on observed associations between patterns of population subdivision and the host of origin of isolates (see review and examples in Walker, ). In a previous (Walker et al ., ) and the present study, we confirmed that most of the genetic variation segregating in B . cinerea populations is explained by hosts, and that the effect of geography is weaker.…”
Section: Discussionsupporting
confidence: 89%
“…The case of bramble ‐ associated isolates is more puzzling, given that populations sampled from this host were differentiated from other populations in a previous study (Walker et al ., ) and partially in this one, but tests did not reveal higher aggressiveness of isolates collected from bramble, compared to isolates from other hosts. Surprisingly, the difference in aggressiveness between tomato ‐ and grapevine ‐ collected strains was observed when inoculating on bramble, whereas it belongs to a botanical family, the Rosaceae, distant from Solanaceae and Vitaceae.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Sexual reproduction has been described for B. cinerea and B. pseudocinerea, but fruiting bodies (apothecia) are only rarely observed in nature. Nevertheless, population genetic studies (41) and the observation of similar frequencies of the mating type alleles MAT1-1 and MAT1-2 (42) have demonstrated that sexual recombination must occur regularly. The existence of both mating types in B. pseudocinerea isolates from the same fields confirms previous suggestions that this species performs sexual reproduction (13).…”
Section: Discussionmentioning
confidence: 99%
“…The B05.10 strain is the Botrytis research community reference, whose genome is fully sequenced (Van Kan et al 2017). Strain VA612 was collected in 2005 in a vineyard in Hautvillers (Champagne, France) from the Pinot Noir cultivar (Walker et al 2015). Strain VA612 was collected in 2005 in a vineyard in Hautvillers (Champagne, France) from the Pinot Noir cultivar (Walker et al 2015).…”
Section: Strains and Microbiological Proceduresmentioning
confidence: 99%